Solteros tóxicos - Steel, Danielle (Plaza y Janés, 2007)
Three daunting bachelors embark on a journey to the Mediterranean where they face women who challenge their deepest relationship phobias, sparking big changes in the once-carefree trio that just might put an end to their carousing days.